Dynamic Processes of an Airport’s System. Applying Value Network Analysis (VNA) to the Air Traveller Experience - Vaz, Margarida; Baltazar, Maria Emília; Silva, Jorge (Journal of Tourism, Sustainability and Well-being, 2015)
In this paper, we argue that networks are fundamental instruments for the development of the business system of airports’ landside area. We propose value network analysis (VNA) to gain a better understanding of how processes and people create value in airports’ network ecosystem. This methodology makes it possible to understand and visualise the internal and external value networks, mapping the players and their interrelationships and thus capturing the dynamics of the airports’ entire system. Applying value network analysis (VNA) to the air traveller experience, we conclude that this approach provides a network ecosystem perspective on how processes and people create value within the air traveller experience network. For the validation of this scenario, several interviews were conducted with experts.